People of the book : an interfaith dialogue about how Jews, Christians and Muslims understand their sacred scriptures /: an interfaith dialogue about how Jews, Christians and Muslims understand their sacred scriptures. (2018) - Cohn-Sherbok, Dan; Chryssides, George D, 1945-; Hasan, Usama
No abstract available